A LUCID PORTRAYAL OF CONSUMMATE LIFE IN ASHALI VARMA’S -THE VICTORIA CROSS - Sayiram (International Journal of Research -GRANTHAALAYAH, 2016)
Army is one of the noblest professions. Army men usually strive for the welfare of our nation. They should be adulated for their unique sacrifice. “The Victoria Cross” throws light on the life of a unique army officer. It is a biography penned by Ashali Varma who might have felt completely satisfied with her portrayal of her parent’s glorious virtues. She has depicted PremBhagat and Mohini who could lead a meaningful life by exchanging love perfectly and exhibiting warmth to the people who have sought succour. Prem was able to attract many people with his humanness. So, he exhibited empathy, gregariousness, veracity and tenacity to make his every endeavour successful. He never pussyfooted. He was down-to- earth. He was true to the adages “The rarer action is in virtue than in vengeance” and “To err is human; to forgive divine” His wife was Mohini. She was an ideal wife to justify a maxim: “There is a woman behind every successful man”. She could shoulder the domestic burden confidently. Her love to her husband is obvious: “I love you more than anything else in this world” (p.no.39). One can find a lot of instances in which Mohini has involved herself voluntarily to buttress PremBhagat even in official affair. She demonstrated her hospitality impeccably. Hence, the book “The Victoria Cross” has been written in eulogy of PremBhagat and Mohini who have proved to be an epitome of a couple.